Pengaruh Model Contextual Teaching and Learning (CTL) Terhadap Hasil Belajar dan Efikasi Diri Peserta Didik Pada Materi Minyak Bumi - Agus Muliaman; Ratna Unaida; Putri Ayu Adurance Simanullang (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine the effect of the contextual teaching and learning model on learning outcomes and students' self-efficacy on petroleum material. The type of research used is a quasi-experimental/quasi-experimental design with a posttest only control group design. The population in this study were all students of class XI SMA Negeri 1 Sawang, while the samples were two classes, namely class XI IPA 1 as the experimental class and class XI IPA 2 as the control class. The data collection instruments in this study were multiple choice tests and self-efficacy questionnaires which were given after the learning treatment for two classes. Testing the data using a non-parametric test assisted by SPSS 18 software. Based on the results of the non-parametric mann-whitney-utest test, it was obtained that it was significant 0.000 < sig level (α = 0.05) this means that H0 is rejected. The results showed that there was an influence of the contextual teaching and learning model on learning outcomes and students' self-efficacy on petroleum material.